COVID-19 Pandemic in Teaching English for Specific Purposes: Impacts on The Remote Teaching Process of Front Office Teachers - Mahendra, I Dewa Gede Oka; Adnyayanti, Ni Luh Putu Era (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Distance teaching is an option for all educators to continue learning activities during the COVID-19 pandemic. This study analyzes how front office teachers in Vocational High Schools implement remote teaching. The participant of this study was a front office teacher at a Vocational High School. This research begins by looking for an overview or making observations to teachers regarding teacher problems in implementing remote teaching. Data was collected qualitatively by using several methods, namely: Observation and Interviews. Data were analyzed through theory with the qualitative descriptive analysis method. The results showed that the most problems faced by teachers when implementing distance teaching were the lack of student response and internet connection problems. Front office teachers must also be able to adapt their teaching strategies to the technology that will be used as a learning medium. The researcher suggests the teacher make an activity that can control the students to practice on how to apply their new knowledge about the material given by the teacher.